2022
DOI: 10.1259/bjr.20220022
|View full text |Cite
|
Sign up to set email alerts
|

Covered stent placement for gastroduodenal artery stump hemorrhage after pancreaticoduodenectomy: long-term patency and risk factor of stent failure

Abstract: Objective: To evaluate the long-term outcomes of covered stent placement in patients with gastroduodenal artery (GDA) stump hemorrhage after pancreaticoduodenectomy (PD) and to identify risk factors of stent failure. Methods and materials: Covered stent was placed in total of 21 patients for GDA stump hemorrhage after PD from September 2012 to March 2021. Technical and clinical success, complications, and stent patency were retrospectively evaluated. Nine relevant variables were analyzed to determine risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Patients with GDA embolization and stent placement were analyzed together because of the high incidence of hepatic arterial occlusion with both procedures. 19,20,22 Data for continuous variables were expressed as median (IQR) and compared between groups using Wilcoxon rank sum and Kruskal-Wallis tests. Data for categorical variables were expressed as number of events (percentage) and compared between groups using Fisher exact tests.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients with GDA embolization and stent placement were analyzed together because of the high incidence of hepatic arterial occlusion with both procedures. 19,20,22 Data for continuous variables were expressed as median (IQR) and compared between groups using Wilcoxon rank sum and Kruskal-Wallis tests. Data for categorical variables were expressed as number of events (percentage) and compared between groups using Fisher exact tests.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated hepatic artery embolization for postoperative bleeding can preserve hepatic flow if there are sufficient arterial collaterals, although there is significant risk of segmental hepatic infarction, which increases with compromised portal vein flow . Additionally, Min et al demonstrated covered stents convey patency rates of 52.9% and 37.8% at 1 and 2 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations